Implementing AppSheet for Digitalizing Inventory and Sales atSalwa Electronics Small Business - Alifia Aura Azzahra; Silvi Anggraeni (Ebiz Prima Nusa, 2025)
Small businesses such asSalwa Electronics facing challenges in inventory and sales management due to inefficient and error-prone manual recording. This project aims to implement a web-based inventory and sales management application.cloud using the platform no-code AppSheet to improve the efficiency and accuracy of data management. The methods used include needs analysis, application design, development, and testing in daily business operations. The application developed is able to record stock in real time, monitor inventory automatically, and display easy-to-understand digital sales reports. With this solution, business owners can access inventory data directly, avoid stock shortages, and manage sales systematically without the need for technical programming skills. Innovation lies in the use of technology no-code as a practical and affordable solution for small businesses in facing digital transformation. This project provides added value in the form of increasing operational efficiency and faster, more accurate data-driven business decision making.